Mother, Can I Trust the Government? Sustained Financial Deepening A Political Institutionsview - Quintyn, Marc (International Monetary Fund, 2010)
Only a minority of countries have succeeded in establishing a developed financial system, despite widespread financial liberalization. Confronted with this finding, the political institutions view claims that sustained financial deepening is most likely to take place in institutional environments where governments effectively impose constraints on their own powers in order to create trust. This paper identifies over 200 post-1960 episodes of accelerations in financial development in a large cross-section of countries. We find that the likelihood of an acceleration leading to sustained financial development increases greatly in environments that have high-quality political institutions